Storage Effects on Microbiological and Some Antioxidant Potentials of Partially Substituted Bread Produced from Wheat Flour and Fresh Coconut Meat - A. I, Akinyede; M. O, Akande; C. Y, Babatuyi; S. O, Oguntuase (Journal of Food Technology Research, 2020)
Bread is a major wheat product consumed in every household because of its easy handling. Fresh coconut meat which is readily available in all rural area in Nigeria may boost both the economy and provide health benefits to those in the rural area. Therefore, the purpose of this study is to evaluate the effect of partial substitution of wheat flour with fresh coconut meat. Wheat flour was partially (90 – 100 %) substituted with 0 –10% fresh coconut meat in the ratio 100 : 0 (WF), 98 : 2 (WFCM1), 96 : 4 (WFCM2), 94 : 6 (WFCM3), 92 : 8 (WFCM4), 90 : 10 (WFCM5). The study evaluated the effects of substitution on proximate composition, sensory characteristics, storage time on some antioxidant potential and microbial stability. Results showed that the overall acceptability of the bread baked from WFCM5 blend was preferred over WF. On the day of production, WFCM5 had the highest phenolic content and total flavonoids but as the days there were reduction in the antioxidant contents of all the bread samples. The microbial load of Nutrient agar, MacConkey agar and Potato dextrose agar increased as the days increased. The bread from the blends may serve as nutritious and potential accepted bread products. The present study confirms effective substitution of wheat flour with fresh coconut meat. The substituted bread showed improved overall acceptability, some antioxidants potentials and microbial stability which may provide health benefits to those in the rural area in Nigeria.